Principles of tourism 2 - Santos, Buen (Quezon City, 2010)
Principles of tourism 2 provides an overview of the major components and variousfactors that shape the tourism industry. These components are discussed as to their nature and structure, and how they interplay to make tourism on of the world's dynamic and fast-rising industries.
Keywords: Tourism; Tourism- Philippines